Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Formal synthesis of (-) anisomycin via organocatalysis - Chouthaiwale, Pandurang V.; Kotkar, Shriram P.; Sudalai, Arumugam (Arkivoc, 2009)
An efficient formal synthesis of (-) anisomycin (1), a potent antibiotic agent, has been achieved in good yields and excellent diastereoselectivity. The key steps are proline-catalyzed sequential alpha-amination or alpha-aminoxylation of aldehyde 2 followed by tandem Horner-Wadsworth-Emmons olefination.
Keywords: alpha-Amination; alpha-aminoxylation; anisomycin; olefination; Proline

Concise enantioselective synthesis of (+)-L-733,060 and (+)-T-2328 via sequential proline catalysis - Lalwani, Komal G.; Sudalai, Arumugam (Synlett, 2016)
A new, sequential proline-catalyzed approach to the synthesis of (+)-L-733,060 and (+)-T-2328 in high optical purity (93% ee) is described starting from phenyl N-Boc imine. The strategy involves proline-catalyzed Mannich reaction of an arylimine with acetaldehyde followed by -aminoxylation/Wittig olefination in a sequential fashion as the key steps.
Keywords: Aminoxylation; imine; Mannich reaction; olefination; sequential

Hypervalent-iodine-mediated base-free oxidative olefination of benzylic amines to access α,β-unsaturated ketones - Rupanawar, Bapurao D.; Bansode, Ajay H.; Suryavanshi, Gurunath (Synlett, 2025)
We report a one-pot base-free protocol for the oxidative olefination of benzylic amines promoted by a hypervalent iodine reagent for the synthesis of alpha,beta-unsaturated ketones. Mechanistically, (diacetoxyiodo)benzene oxidizes the benzylic amine to the corresponding imine, which, on reaction with a phenacyl(triphenyl)phosphonium bromide salt and an in situ generated acetoxy anion leads to an alpha,beta-unsaturated ketone. A wide range of alpha,beta-unsaturated ketones were easily accessed through direct oxidative olefination of substituted benzylic amines in good to excellent yields and with high E -selectivity.
Keywords: benzylic amines; enones; hypervalent iodine; olefination; Oxidation